PEMETAAN ZNT MELALUI ANALISIS NILAI TANAH SEBAGAI ASET BANGSA - Daeli, Serta Denius (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2024)
Land as a national asset must receive attention in terms of distribution and ownership. Therefore analysis is very important to support Land Value Zoning (ZNT) mapping. In practice, there are various factors that influence land price determination and these factors must be taken into consideration. Because the position of the land determines the value of the land, especially those in disaster-prone areas. Its importance is not only for buying and selling transactions but in making decisions related to infrastructure development and risk mitigation. Based on these conditions, this research aims to analyze the influence of the factors analyzed including the distance of the object from the main road, the distance of the object to the central business district (CBD), and the width of the road. The factors that influence land value are studied using the multiple regression method. The method used in this research uses a quantitative approach with a multiple regression research design. The analysis results show that distance to the CBD, distance to the main road, and road width have a positive and significant influence on land value with an influence of 69.2%. The remaining 30.8% was influenced by other factors not studied.